EFFECT OF HYDROXYETHYLCELLULOSE ON THE RELEASE OF GLIBENCLAMIDE FROM SUSTAINED RELEASE TABLETS - S. V. Trofimov (Разработка и регистрация лекарственных средств, 2019)
With this study the results of influence particle size distribution and method of modification API on dissolution profile from matrix tablets with sustained release are shown. The effect of Hydroxyethylcellulose, which is used as sustained release agent, also as an excipient, able to improve dissolution speed and maintain more complete release of an API from sustained release formulation, with glibenclamide as an example has been studied.